2021
DOI: 10.7554/elife.70119
|View full text |Cite
|
Sign up to set email alerts
|

The BigBrainWarp toolbox for integration of BigBrain 3D histology with multimodal neuroimaging

Abstract: Neuroimaging stands to benefit from emerging ultrahigh-resolution 3D histological atlases of the human brain; the first of which is 'BigBrain'. Here, we review recent methodological advances for the integration of BigBrain with multi-modal neuroimaging and introduce a toolbox, 'BigBrainWarp', that combines these developments. The aim of BigBrainWarp is to simplify workflows and support the adoption of best practices. This is accomplished with a simple wrapper function that allows users to easily map data betwe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 101 publications
(154 reference statements)
0
76
0
Order By: Relevance
“…The combination of post mortem microscopy and in vivo imaging depends upon precise mapping between atlases. The present work leveraged a specialised multi-modal surface matching procedure (Lewis et al, 2020;Paquola et al, 2021), which minimises the misregistration error of landmarks to approximately 4mm, on par with standard in vivo registrations. The issue of precise mapping of functional networks to the BigBrain is further complicated by subject-specificity of functional network topographies (Braga and Buckner, 2017;Kong et al, 2019;Seitzman et al, 2019) and the impossibility of defining subject-specific functional networks on BigBrain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of post mortem microscopy and in vivo imaging depends upon precise mapping between atlases. The present work leveraged a specialised multi-modal surface matching procedure (Lewis et al, 2020;Paquola et al, 2021), which minimises the misregistration error of landmarks to approximately 4mm, on par with standard in vivo registrations. The issue of precise mapping of functional networks to the BigBrain is further complicated by subject-specificity of functional network topographies (Braga and Buckner, 2017;Kong et al, 2019;Seitzman et al, 2019) and the impossibility of defining subject-specific functional networks on BigBrain.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, surfacewise smoothing was performed at each depth independently and involved moving a 2-vertex FWHM Gaussian kernel across the surface mesh using SurfStat . The staining intensity profiles are made available in the BigBrainWarp toolbox [(https://github.com/caseypaquola/BigBrainWarp), (Paquola et al, 2021)].…”
Section: Histological Datamentioning
confidence: 99%
“…Thus, functional images were processed using a top-performing preprocessing pipeline implemented using the eXtensible Connectivity Pipeline (XCP) Engine 83 , which includes tools from FSL 92,94 and AFNI 95 . This pipeline included (1) correction for distortions induced by magnetic field inhomogeneity using FSL's FUGUE utility, (2) removal of 4 initial volumes, (3) realignment of all volumes to a selected reference volume using FSL's MCFLIRT, (4) interpolation of intensity outliers in each voxel's time series using AFNI's 3dDespike utility, (5) demeaning and removal of any linear or quadratic trends, and (6) co-registration of functional data to the high-resolution structural image using boundarybased registration. Images were de-noised using a 36-parameter confound regression model that has been shown to minimize associations with motion artifact while retaining signals of interest in distinct sub-networks 83,96 .…”
Section: Rs-fmri Processingmentioning
confidence: 99%
“…This structural model suggests that the degree to which two regions share similar cytoarchitectural features predicts the distribution of their laminar projections. Critically, inter-regional similarity in cytoarchitecture varies gradually across the cortex, creating a sensory-fugal (S-F) axis 5,6 that predicts regions' profiles of extrinsic connectivity to the rest of the brain. This gradient positions contiguous visual and sensorimotor cortex at one end and distributed heteromodal association and paralimbic cortices at the other, and is correlated with other macroscopic gradients of brain structure and function [7][8][9][10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has shown that the analysis of covariance patterns of intracortical microstructural profiles can generate new descriptions of large-scale network organization (Paquola et al, 2020; Royer et al, 2020). These networks appear to be primarily governed by systematic shifts in laminar differentiation and neuronal density, showing a principal organizational axes similar to those at the level of cytoarchitecture and intrinsic functional connectivity (Margulies et al, 2016; Paquola et al, 2021, 2019b). A further notable feature is the automated generation of cortico-cortical geodesic distance matrices, which indexes proximity between different regions on the folded cortical surface.…”
Section: Discussionmentioning
confidence: 92%